Les Salafistes and a French Reproduction of Certainties in a World of Uncertainties - Emin Poljarevic (International Institute of Islamic Thought, 2016)
The new French documentary Les Salafistes (The Salafis) that premiered January 26, 2016, in a small number of French theaters offers iconographic imagery seldom seen in the public space: a string of interviews with some of the leading jihadist militants in Mali, Tunisia, Algeria, and Iraq coupled with ghastly images of violence perpetrated by militant groups. The intention appears to be to show the irrationality of and paradox in the jihadis’ discourse and actions. Unfortunately, the directors have succeeded only in reproducing already existing stereotypes of Salafis. The lack of any appropriate contextualization that problematizes the recent rise of violence in the Middle East and North Africa (MENA) region is perhaps the film’s major flaw. Despite the directors’ ambition to let violent extremists discredit their own project, the documentary presents an essentialist argument that reproduces Orientalist imageries of a savage religion. Without the appropriate commentary and background overview to the conflicts featured in the film, the audiences are left alone with an extremist narrative that confirms the evocations of the West’s moral, cultural, and political superiority over the East.